Comparison of selective hydrolysis of α-lactalbumin by acid Protease A and Protease M as alternative to pepsin: potential for β-lactoglobulin purification in whey proteins. Issue 1 (7th February 2019) - Lisak Jakopović, Katarina; Cheison, Seronei Chelulei; Kulozik, Ulrich; Božanić, Rajka
Abstract: The experiments reported in this research paper examine the potential of digestion using acidic enzymes Protease A and Protease M to selectively hydrolyse α-lactalbumin (α-La) whilst leaving β-lactoglobulin (β-Lg) relatively intact. Both enzymes were compared with pepsin hydrolysis since its selectivity to different whey proteins is known. Analysis of the hydrolysis environment showed that the pH and temperature play a significant role in determining the best conditions for achievement of hydrolysis, irrespective of which enzyme was used. Whey protein isolate (WPI) was hydrolysed using pepsin, Acid Protease A and Protease M by randomized hydrolysis conditions. Reversed-phase high performance liquid chromatography was used to analyse residual proteins. Regarding enzyme selectivity under various milieu conditions, all three enzymes showed similarities in the reaction progress and their potential for β-Lg isolation.